2001
DOI: 10.1177/000331970105200306
|View full text |Cite
|
Sign up to set email alerts
|

The 1999 French Venous Disease Survey: Epidemiology, Management, and Patient Profiles

Abstract: A recent (1999) Sofres survey of representative samples of the adult French population aged 15 and over showed that almost half this population suffered from lower limb venous complaints and that 43% of them were untreated. Of those treated, 24.2% received venotropics, including 21.5% by prescription, while 6.0% practiced self-medication. Venous disease sufferers form a relatively underprivileged sector of the population in terms not only of age, income, work and living conditions, but also of general health a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…This elevated risk may result from their hot and humid workplace conditions. In addition, socio-economic factors may be implicated: some studies have reported a higher prevalence of venous disease in the relatively underprivileged sector of the population [31][32][33], although no relation between the epidemiology of CVD and social class was found in the Edinburgh vein study [34].…”
Section: Discussionmentioning
confidence: 99%
“…This elevated risk may result from their hot and humid workplace conditions. In addition, socio-economic factors may be implicated: some studies have reported a higher prevalence of venous disease in the relatively underprivileged sector of the population [31][32][33], although no relation between the epidemiology of CVD and social class was found in the Edinburgh vein study [34].…”
Section: Discussionmentioning
confidence: 99%
“…Even though it is a very common disease, due to the lack of epidemiological data, the prevalence of CVI cannot be inferred. Previous studies have recorded specific characteristics in advanced cases, including patients who presented to the hospital and were diagnosed with varicose veins and leg ulcers 15 , 16 ) . In our study, we only evaluated patients in the early stage of the disease (CEAP classification stage 1 and 2) to ensure a homogenous patient distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, venotonic drugs are still widely used for the treatment of venolymphatic insufficiency and haemorrhoids in France. 1 Venous problems frequently occur during pregnancy, often leading to the prescription of these drugs. One previous study 2 showed that 20% of French women were prescribed hesperidin, and a similar percentage received diosmin, during pregnancy.…”
Section: Introductionmentioning
confidence: 99%